PERILAKU HIDUP BERSIH DAN SEHAT SELAMA PANDEMI COVID-19 UNTUK MENINGKATKAN KUALITAS KESEHATAN BAGI SISWA SD GMIT PUKDALE KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Brigita Dina Manek; Matilda Bupu Ria; Nabilah Nurul Ilma; Atalia Pili Mangngi (Jurnal Pengabdian Ilmu Kesehatan, 2022)
Clean and Healthy Living Behavior is a reflection of the family lifestyle that always pays attention to and maintains the health of all family members. Community service activities in this case health socialization at SD GMIT Pukdale will be held on Tuesday, 5 April 2022, starting at 08.00 WITA. As implementing staff are 4 supervisors of D-III Midwifery STIKes Maranatha Kupang. The number of students at GMIT Pukdale Elementary School who participated in the socialization was 60 people. The activity began with an opening by the principal, followed by an introduction to the implementation team of the activity. The socialization was opened by the team leader by explaining the purpose and objectives of socializing Clean and Healthy Living Behavior. Before starting, the team leader gave the questions as a pre-test to the audience. Then socialization is carried out by 1-3 speakers. Before the socialization ends, the extension team provides questions as a form of post-test. Then the activity was initiated by the supervisor of GMIT Pukdale Elementary School.